Re-shaping King Lear: Space, Place, Costume, and Genre - Hattaway Michael (Linguaculture, 2017)
Performance studies must enjoy parity of esteem with critical studies because they remind us of the plurality of “readings” that are generated by a Shakespearean text. Shakespeare seems to have apprehended this when, in Othello, he used a nonce-word, “denotement”, which applies to Othello’s reading of his wife in his mind’s eye. I examine other sequences in which we watch a character “reading” on-stage or imagined action, in Hamlet, Titus Andronicus, Cymbeline, Richard II, and Troilus and Cressida. In Hamlet this involves re-reading as well as generic displacement, which, I argue, is a way of rendering inwardness. As I test case, I analyse a production of King Lear by Shakespeare’s Globe, on a fairground stage, in which the king reshaped himself, became a folkloric figure, like a figure in Nashe’s Summer’s Last Will and Testament. The play itself was thus, indecorously, reshaped as “The Tale of King Lear”. “Dramatic truth”, therefore, in no way depends upon theatrical “realism”.